Christianity and private law - Cochran, Robert F., 1951-; Moreland, Michael P. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This volume examines the relationship between Christian legal theory and the fields of private law. Recent years have seen a resurgence of interest in private law theory, and this book contributes to that discussion by drawing on the historical, theological, and philosophical resources of the Christian tradition. The book begins with an introduction from the editors that lays out the understanding of "private law" and what distinguishes private law topics from other fields of law. This section includes two survey chapters on natural law and biblical sources. The remaining sections of the book move sequentially through the fields of property, contracts, and torts. Several chapters focus on historical sources and show the ways in which the evolution of legal doctrine in areas of private law has been heavily influenced by Christian thinkers. Other essays draw out more contemporary and public policy-related implications for private law"--
Introduction -- Property -- Contracts -- Torts.
OCLC-licensed vendor bibliographic record.
Keywords: Christianity and law -- History; Religion and law; Christianity -- Philosophy; Civil law; HISTORY / Social History; LAW / General; LAW / Administrative Law & Regulatory Practice